THE FATWAS OF AHMAD KHATIB MINANGKABAU (1860-1916) AND RELIGIOUS AUTHORITY IN INDONESIA - J.G. Kaptein, Nico (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2024)
Ahmad Khatib originated from Minangkabau, West Sumatra and after his settlement in the Holy City of Mecca in 1877, he grew into a scholar in Islamic sciences of great repute and eventually died there in 1916. His written work, educational and other activities have played a vital part in the exchange of religious ideas between Mecca and the Malay-Indonesian archipelago and make him an important person in the history of Islam in Southeast Asia. In my paper I will go in detail into a fatwa he gave on the question of whether or not it was allowed to sell chickens to Chinese. The paper aims to shed light on the mufti-ship of Ahmad Khatib and will look into the wider implications of the issue as far as religious authority is concerned, in particular into its locus.